IMPROVING THE EFFECTIVENESS OF EDUCATION AND THE IMPLEMENTING INNOVATIVE EDUCATIONAL TECHNOLOGIES IN THE EDUCATIONAL PROCESS - Ortiqova Maftuna Komiljon qizi; Toshmatova Sitora Ravshanovna (Ta'lim innovatsiyasi va integratsiyasi, 2023)
Abstract: In this article, the application of interactive learning technologies in the educational process can improve the quality of education, increase its effectiveness, determine the interaction between teacher, student, student group, as well as the community, achieve ideological and spiritual unity, striving for a common goal. It was noted that it has the necessary conditions and a great opportunity to create the environment for its realization as a person.